How the rise of academic families across cohorts influences sons’ and daughters’ tertiary education in West Germany? - Blossfeld, Pia Nicoletta (Frontiers in Education, 2023)
In this article, we examine how the rising proportion of academic families across cohorts affects sons’ and daughters’ tertiary educational attainment in the process of educational expansion. Using data from the National Educational Panel Study (NEPS), we focus on West Germany and examine whether the upgrading of the educational composition of families across cohorts has particularly contributed to daughters catching up with and even overtaking sons in tertiary educational attainment over time, or whether daughters and sons have benefited equally. In particular, we ask whether the rise of academic families, who are assumed to have stronger gender-egalitarian attitudes toward their children, has contributed to daughters faster increase in tertiary education compared to sons. Our empirical analysis shows that the long-term upgrading of families’ education across cohorts has in a similar manner increased tertiary educational attainment of both sons and daughters. Thus, women’s educational catch-up process cannot be explained by the greater gender-egalitarian focus of acadeic parents. Rather all origin families, independent of their educational level, are following the same secular trend towards more gender egalitarianism. We also examine to which extent highly qualified mothers serve as role models for their daughters. We find that academic mothers do not serve as particular role models for their daughters. Rather mother’s education is equally important for both sons’ and daughters’ success in higher education. Finally, we show that the rising proportion of academic families across cohorts is connected to a rising proportion of downward mobility for both sons and daughters. However, the share of upward mobile daughters from non-academic families is converging with that of sons.